Faktor yang Mempengaruhi Kepuasan Konsumen Muslim di Hos Coffe Kartasura - Permadi, Muhammad (Universitas Negeri Surabaya, 2022)
The growth of the cafe business in Indonesia is growing rapidly, as well as in the Sukoharjo area. Various cafe concepts are currently provided with various concepts so as to attract consumers' buying attention and ultimately increase customer satisfaction. The purpose of this research is to analyze the factors that influence consumer satisfaction of Hos Coffee. This type of quantitative descriptive research with research objects are all consumers of Hos Coffee Kartasura with a sample of 92 people taken by accidental sampling. Data collection techniques using a questionnaire. The data analysis technique used multiple linear regression analysis. The results of multiple linear regression analysis showed product quality, service quality, price and emotional factors had a significant effect on Hos Coffee consumer satisfaction (p < 0.05). So it is suggested that the management of Hos Coffee Kartasura can pay more attention to the preparation of strategies that are able to maintain and develop businesses, especially coffee shops seen from product quality, service quality, price and consumer emotional factors.